Persons, Personalism, and the 1979 Peruvian Constitution - Fernández Sessarego, Carlos (1982)
This article offers an analysis of the evolution of the legal protection of the fundamental rights of the individual, from the 1933 Constitution to the promulgation of the 1979 Constitution. It begins with a critique of the 1933 Constitution and the 1936 Civil Code, which did not have an organic and systematic regulation of the fundamental rights of the individual, nor a clear definition of their relationship with the State and society. Influenced by philosophical currents such as existentialism and Marxist humanism, a theoretical development of the concept of the person began in the 1940s. This personalist approach was reflected in the proposed reform of the Civil Code in 1965, culminating in the draft of the First Book “Of Persons” in 1967. Subsequently, the 1979 Constitution marked a significant change by explicitly recognizing the person as the supreme purpose of society and the State, establishing fundamental rights and a vision of work as a social right and duty. In addition, it promoted the compulsory teaching of the Constitution and human rights. Based on all this, the author celebrates this Constitution as a milestone in Peruvian history, by integrating personalist principles that place the person at the center of the legal system, promoting a just and supportive society.